Chapter Michael Marullus Tarchaniota's De laudibus Rhacusae and His Early Years - Vedran (Biblioteca di Studi Slavistici, 2020)
This paper deals with Michael Marullus Tarchaniota's early childhood years marked by exile from the recently fallen Despotate of Morea, a short and unconfirmed stay in Dubrovnik and, finally, by his arrival in Naples. A vast array of heterogeneous sources have been sifted in order to elucidate Marullus' life before his arrival in Naples, i.e. in the turbulent period marked with Ottoman advance into the heart of Europe. The second part of this paper deals with Marullus' De laudibus Rhacusae , which speaks more about the broader political context than about Dubrovnik itself since inspired by the turmoil that affected entire Apennine peninsula of that time.